Pemilihan Aplikasi Meeting Online Untuk Mendukung Work From Home Menggunakan Metode AHP - Danang, Deodatus; Mustika, Wida Prima; Merdekawati, Agustiena (STIKOM Tunas Bangsa Pematangsiantar, 2020)
The Indonesia government has started to prepare the strategies by setting the new policies regarding the spread of the coronavirus (Covid-19) since the first case was found on March, 2nd 2020. One of those policies is appealing to all government staffs/State C3il Apparatus and pr3ate employees to apply the system of remote working (Work from Home). To support the act3ity of remote working, the employees have been using some applications for online meetings to communicate with colleagues, superiors, and business partners in resolving the workloads without direct physical contacts. These applications needed are Zoom, Google Meet, Skype, and Webex. The writer conducted a study using the Analytical Hierarchy Process (AHP) method to determine the selection of the appropriate application for online meetings according to the priority criteria required by the employees who work at home. AHP method can provide the best order that will produce criteria and alternat3es with the highest values. The research was conducted based on the criteria for application features, ease of use, number of participants, duration of time, bandwidth requirements, and application security. The result for alternat3es with priority results was the Zoom application with the highest value of 0.341 (34.1%), followed by Google Meet with a value of 0.319 (31.9%), Skype with a value of 0.187 (18.7%), and Webex. With a value of 0.153 (15.3%) as the lowest order.